2019
DOI: 10.1002/cmm4.1063
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐preserving numerical scheme for the one‐phase Hele‐Shaw problems by the method of fundamental solutions

Abstract: In this study, the solutions to the one‐phase interior or the classical Hele‐Shaw problem are discretized in space by employing the method of fundamental solutions combined with the uniform distribution method; furthermore, a system of ordinary differential equations is obtained, which is solved using the usual fourth‐order Runge‐Kutta method. The one‐phase interior Hele‐Shaw problem has curve‐shortening (CS), area‐preserving (AP), and barycenter‐fixed (BF) properties. Under our numerical scheme, a discrete ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Typical examples include the mean curvature flow [34], areapreserving mean curvature flow [10], and Hele-Shaw flow [20]. We note that it was proved in [11,10,12,14] that the first two examples do not allow any topological changes during the evolution, and numerical observations suggested that the same property holds for the Hele-Shaw flow [38].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Typical examples include the mean curvature flow [34], areapreserving mean curvature flow [10], and Hele-Shaw flow [20]. We note that it was proved in [11,10,12,14] that the first two examples do not allow any topological changes during the evolution, and numerical observations suggested that the same property holds for the Hele-Shaw flow [38].…”
Section: Introductionmentioning
confidence: 78%
“…In this section, we discretize the moving boundary problem (1.1) in space. The discretization is based on [38,41]. Below we give definitions of discrete tangent vectors, discrete outward normal vectors, discrete curvatures, discrete tangential velocities and discrete normal velocities.…”
Section: Semi-discrete Polygonal Moving Boundary Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…where f is a given data. The invariant scheme of the method of fundamental solutions (MFS) with weighted average condition and dummy points offers an approximate solution for (1a)-(1b) as in the following procedure [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we can add one more condition such as the weighted average condition (3), which is nothing but the invariant condition (6) when all weights H j are equal to 1. Our modifications (3)-(4) enable us to construct some geometrical structure-preserving numerical scheme for the one-phase Hele-Shaw problem [1,2], which is a moving boundary problem.…”
Section: Introductionmentioning
confidence: 99%